Peran Kepuasan Kerja dalam Memediasi Pengaruh Lingkungan Kerja dan Beban Kerja terhadap Loyalitas Karyawan: (Studi pada Divisi Kepatuhan PT Permodalan Nasional Madani) - Kheyla Trinanda Agustina; Syaiful Anwar (JURNAL RISET MANAJEMEN (JURMA), 2025)
This research aims to examine the role of job satisfaction in mediating the influence of the work environment and workload on employee loyalty, a study in the compliance division of PT Permodalan Nasional Madani, South Jakarta. The method used is descriptive quantitative using a questionnaire. The analysis technique used in this research is Path Analysis. Sampling in this study used nonprobability sampling techniques and used the census or total method. with a total sample of 38 respondents. Data was collected through a questionnaire with an interval scale which was processed using Microsoft Excel 2019 software and SmartPLS version 4.1.0.2. The results of this research show that work environment variables have no effect on employee loyalty. The workload variable has a positive and significant effect on employee loyalty. The job satisfaction variable has a positive and significant effect on employee loyalty. Work environment variables have a positive and significant effect on job satisfaction. The workload variable has a positive and significant effect on job satisfaction. The job satisfaction variable is able to mediate the work environment variable on employee loyalty. The job satisfaction variable is not able to mediate workload on employee loyalty. This research examines the important role of management in creating a conducive work environment.